The Effect Of Digital Marketing And Product Variety On Purchasing Decisions Mediated By Brand Image In Bakso President - Rike Selviasari; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Jurnal Riset dan Inovasi Manajemen, 2023)
This study aims to investigate the effect of digital marketing (X1) and product variety (X2) on purchasing decisions (Y) with brand image (Z) as a mediator in the context of Micro, Small and Medium Enterprises (MSMEs) in Malang City, namely Bakso President. The population of this study were Instagram and Tiktok followers and the sample of this study were 327 respondents. This research technique uses proportional random sampling. This research analysis uses SEM-PLS. The results of this study highlight the importance of a thoughtful digital marketing strategy and high-quality product variety in building a strong brand image. The findings also underline that a positive brand image has a positive impact on consumer purchasing decisions at Bakso President. The practical implication is that MSMEs can utilize brand image as a strategic asset to improve their competitiveness and business growth.